The Physical Expression of Emotional Suffering in Hávarðar saga Ísfirðings: Uncovering Pain in the Íslendingasögur. - Ebbs, Eira Kathleen (Scandinavian Studies, 2025)
With an increasing interest in the history of emotions, the experience of painful feelings is being investigated more thoroughly in a wide variety of medieval sources. The Íslendingasögur focus primarily on elite men, for and by whom open expressions of emotional suffering are usually considered shameful and are therefore quite rare. Even so, there are instances in which their bodies offer the reader a glimpse of their inner feelings. The article examines the communication of masculine bereavement through behaviors associated with corporeal pain or sickness and how this reveals attitudes toward physical and emotional distress as well as the ways in which their demonstration and interpretation are influenced by social factors such as age, class, and gender.